2017
DOI: 10.1002/app.45673
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial nanocomposites and electrospun coatings based on poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) and copper oxide nanoparticles for active packaging and coating applications

Abstract: Active biodegradable poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) melt mixed nanocomposites and bilayer structures containing cooper oxide (CuO) nanoparticles were developed and characterized. The bilayer structures consisted of a bottom layer of compression molded PHBV3 (3% mol valerate) coated with an active electrospun fibers mat made with microbial mixed culture derived PHBV18 (18 % valerate) and CuO nanoparticles. The results showed that the oxygen barrier properties were slightly enhanced by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 39 publications
6
44
0
Order By: Relevance
“…As reported for other antimicrobial materials, higher antibacterial activity against Salmonella enterica and Listeria monocytogenes was recorded under the same experimental conditions (Castro‐Mayorga et al., ).…”
Section: Development Of Food‐grade Polymers and Biopolymers With Antisupporting
confidence: 79%
See 1 more Smart Citation
“…As reported for other antimicrobial materials, higher antibacterial activity against Salmonella enterica and Listeria monocytogenes was recorded under the same experimental conditions (Castro‐Mayorga et al., ).…”
Section: Development Of Food‐grade Polymers and Biopolymers With Antisupporting
confidence: 79%
“…Castro‐Mayorga, Fabra Rovira, Cabedo Mas, Sánchez Moragas, and Lagarón Cabello () recently developed and characterized 2 active copper‐based systems performing interesting antiviral activity. In their study, the antiviral activity of biodegradable PHBV melt mixed nanocomposites containing 0.1% and 0.05% of CuO was compared to bilayer structures consisting of a bottom layer of compression molded PHBV3 (3% mol valerate) coated with an active electrospun fibers layer made with microbial mixed culture‐derived PHBV18 (18% valerate) and CuO nanoparticles (0.05%).…”
Section: Development Of Food‐grade Polymers and Biopolymers With Antimentioning
confidence: 99%
“…In comparison with other previous studies, the here-studied PHBV films exhibited a lower melting profile than other PHBV films prepared by solving casting, i.e., T m values at 145-157 • C for HV 12 mol.-% (Sanchez-Garcia et al, 2008). Similarly, PHBV materials with HVs of 3 and 18 mol.-% prepared by melt mixing also showed higher T m values, i.e., 169.6 and 173.2 • C, and T c values, i.e., 107.1 • C (Castro Mayorga et al, 2018). In relation to other electrospun films, (Cherpinski et al, 2018) reported two melting points at 162.2 and 177.3 • C for PHB films while T c was 110.4 • C. The lower values in the present study can be related to the higher HV content of the here-processed PHBV materials.…”
Section: Thermal Propertiesmentioning
confidence: 84%
“…WAXD experiments were conducted on both films and fiber mats obtained from samples 6 and 7 to assess their crystallinity since DSC, being a dynamic method, does not provide an accurate description of crystallinity for this biopolymer as discussed earlier (Cherpinski et al, 2017;Castro Mayorga et al, 2018). The diffractograms, included in Figure 7, presented two main peaks located at 13.5 • and 16.9 • (2θ), followed by three other minor reflections at ca.…”
Section: Crystallinitymentioning
confidence: 99%
See 1 more Smart Citation